Disentangling Natural and Anthropogenic Signals in Lacustrine Records: An Example from the Ilan Plain, NE Taiwan - Huang, Jyh-Jaan; Huh, Chih-An; Wei, Kuo-Yen; Löwemark, Ludvig; Lin, Shu-Fen; Liao, Wen-Hsuan; Yang, Tien-Nan; Song, Sheng-Rong; Lee, Meng-Yang; Su, Chih-Chieh; Lee, Teh-Quei (Frontiers in Earth Science, 2016)
The impact of human activities has been increasing to a degree where humans now outcompete many natural processes. When interpreting environmental and climatic changes recorded in natural archives on historical time scales, it is therefore important to be able to disentangle the relative contribution of natural and anthropogenic processes. Lake Meihua on the Ilan Plain in northeastern Taiwan offers a particularly suitable opportunity to test how human activities known from historical records can be recorded in lacustrine sediment. For this purpose, three cores from Lake Meihua have been studied by a multiproxy approach, providing the first decadal-resolution lacustrine records covering the past 150 years in Taiwan. Profiles of excess 210Pb, 137Cs and 239, 240Pu from two short cores (MHL-09-01 and MHL-11-02) allowed a precise chronology to be established. The presence of a yellow, earthy layer with lower levels of organic material coincide with the record of land development associated with the construction of the San-Chin-Gong Temple during AD 1970–1982. Furthermore, in the lower part of the cores, the upwards increasing trend of inc/coh, TOC, TOC/TN, and grain size, coupled with the palynological data (increase of Alnus, Mallotus, Trema and herbs) from the nearby core MHL-5A with radiocarbon chronology, suggest that the area surrounding the lake has been significantly affected by agricultural activities since the arrival of Chinese settlers around ~AD 1874. In sum, this study demonstrates that this suite of lacustrine sediments in northeastern Taiwan has recorded human activities in agreement with historical documents, and that different human activities will leave distinct sedimentological, geochemical, and palynological signatures in the sedimentary archives. Therefore, multiproxy reconstructions are important to capture the complex nature of human-environmental interactions. A better understanding of the weathering and erosion response to human activities can also provide useful information for sustainable land-use management.